Second Opinions in Markets for Expert Services: Experimental Evidence - Wanda Mimra; Alexander Rasch; Christian Waibel (ETH Zurich, CER-ETH - Center of Economic Research, 2016)
We experimentally investigate the role of second opinions in markets where experts like doctors both diagnose and provide the services. Experts may exploit their informational advantage over customers and overtreat by providing a more costly and expensive treatment than necessary. We show that introducing costly second opinions significantly reduces the level of overtreatment. Market efficiency rises as the reduction in treatment costs—due to less overtreatment—exceeds the increase in incurred search costs. Lowering customers' search costs leads to significantly more second opinions, however, the overtreatment level does not decrease.
Keywords: D82; L15; 330; Credence goods; Experts; Second opinion; Overtreatment; Search costs